(untitled) - NICOLAISEN, NANCY (USA, 1994)
1.Using appwizard / 2.Using the integrated development environment / 3.Acookbook approach to creating windows applications / 4.Alphabetical reference to the Microsoft foundaton classes C++ library
Incluye indice analitico pag.855
Keywords: LENGUAJES DE PROGRAMACION - C++